Haplotypic Associations and Differentiation of MHC Class II Polymorphic Alu Insertions at Five Loci With HLA-DRB1 Alleles in 12 Minority Ethnic Populations in China - Cun, Yina; Shi, Lei; Kulski, Jerzy K.; Liu, Shuyuan; Yang, Jia; Tao, Yufen; Zhang, Xinwen; Shi, Li; Yao, Yufeng (Frontiers in Genetics, 2021)
The analysis of polymorphic variations in the human Major Histocompatibility Complex (MHC) class II genomic region on the short-arm of chromosome 6 is a scientific enquiry to better understand the diversity in population structure and the effects of evolutionary processes such as recombination, mutation, genetic drift, demographic history, and natural selection. In order to investigate associations between the polymorphisms of HLA-DRB1 gene and recent Alu insertions (POALINs) in the HLA class II region, we genotyped HLA-DRB1 and five Alu loci (AluDPB2, AluDQA2, AluDQA1, AluDRB1, AluORF10), and determined their allele frequencies and haplotypic associations in 12 minority ethnic populations in China. There were 42 different HLA-DRB1 alleles for ethnic Chinese ranging from 12 alleles in the Jinuo to 28 in the Yugur with only DRB1*08:03, DRB1*09:01, DRB1*12:02, DRB1*14:01, DRB1*15:01, and DRB1*15:02 present in all ethnic groups. The POALINs varied in frequency between 0.279-0.514 for AluDPB2, 0-0.127 for AluDQA2, 0.777-0.995 for AluDQA1, 0.1-0.455 for AluDRB1 and 0.084-0.368 for AluORF10. By comparing the data of the five-loci POALIN in 13 Chinese ethnic populations (including Han-Yunnan published data) against Japanese and Caucasian published data, marked differences were observed between the populations at the allelic or haplotypic levels. Five POALIN loci were in significant linkage disequilibrium with HLA-DRB1 in different populations and AluDQA1 had the highest percentage association with most of the HLA-DRB1 alleles, whereas the nearby AluDRB1 indel was strongly haplotypic for only DRB1*01, DRB1*10, DRB1*15 and DRB1*16. There were 30 five-locus POALIN haplotypes inferred in all populations with H5 (no Alu insertions except for AluDQA1) and H21 (only AluDPB2 and AluDQA1 insertions) as the two predominant haplotypes. Neighbor joining trees and principal component analyses of the Alu and HLA-DRB1 polymorphisms showed that genetic diversity of these genomic markers is associated strongly with the population characteristics of language family, migration and sociality. This comparative study of HLA-DRB1 alleles and multilocus, lineage POALIN frequencies of Chinese ethnic populations confirmed that POALINs whether investigated alone or together with the HLA class II alleles are informative genetic and evolutionary markers for the identification of allele and haplotype lineages and genetic variations within the same and/or different populations.